Hydrogels in a historical perspective: From simple networks to smart materials - Buwalda, Sytze J.; Boere, Kristel W M; Dijkstra, Pieter J.; Feijen, Jan; Vermonden, Tina; Hennink, Wim E. (Elsevier BV, 2014)
Over the past decades, significant progress has been made in the field of hydrogels as functional biomaterials. Biomedical application of hydrogels was initially hindered by the toxicity of crosslinking agents and limitations of hydrogel formation under physiological conditions. Emerging knowledge in polymer chemistry and increased understanding of biological processes resulted in the design of versatile materials and minimally invasive therapies. Hydrogel matrices comprise a wide range of natural and synthetic polymers held together by a variety of physical or chemical crosslinks. With their capacity to embed pharmaceutical agents in their hydrophilic crosslinked network, hydrogels form promising materials for controlled drug release and tissue engineering. Despite all their beneficial properties, there are still several challenges to overcome for clinical translation. In this review, we provide a historical overview of the developments in hydrogel research from simple networks to smart materials.
Keywords: Biomaterials; Controlled release; Drug delivery; Historical overview; Hydrogels; Polymer science; Pharmaceutical Science